Penerapan Etika Profesi Akuntan dan Kasus-Kasus Pelanggaran Etika Bisnis dalam Profesi Akuntan - Syahara Attari Said; Indah Suntika; Cynintya Agness (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Every profession definitely has ethics or regulations that a company must comply with. Having ethics in a company can build trust between the company, employees, customers and other stakeholders. Therefore, the author will discuss a little about ethics and most importantly ethics related to the accounting profession. Accounting work includes various tasks and responsibilities carried out by accountants in organizations. In this article, the method used is the literature method. The literature method or library study is carried out by searching for data or information through reading scientific journals, reference books and published materials available in libraries or the internet. This research is descriptive in nature, which means that the data obtained is explained systematically, then analyzed and explained so that it is easy for readers to understand. In the field of accounting, there are ethics that must be adhered to by each member. The Code of Ethics of the Indonesian Accountants Association (IAI) functions as a guide and rules for all its members, whether practicing as public accountants, working in the business sector, government agencies, or in the world of education. This guide is designed to assist accountants in fulfilling their professional responsibilities. By applying these ethical principles, accounting practitioners can ensure that they carry out their duties with integrity, transparency and competence, thereby supporting public trust and the sustainability of the accounting profession. By implementing these suggestions, it is hoped that accounting practitioners will be better able to carry out their duties with integrity and transparency, thereby supporting the sustainability of the accounting profession and building stronger public trust